Industry concentration, stock returns and asset pricing: The UK evidence - Sulaiman Mouselli; Aziz Jaafar (Cogent Economics & Finance, 2019)
How does competition in firms' product markets influence stock returns? We examine this question using firms domiciled in the UK. We find that firms in less concentrated industries earn higher returns, even after controlling for the well-known determinants of the cross-section of UK stock returns. Furthermore, we suggest a novel asset pricing model that explicitly incorporates industry concentration as a distinguished risk factor capturing important features of product markets. Our results link the explanatory power of R&D activity of stock returns to product market structure. Also, we suggest an explanation for value premium on the basis of product market structure that favours barriers to entry interpretation for the higher returns obtained by less concentrated industries.
Keywords: G1; G12; 330; market structure; industry concentration; stock returns; asset pricing